Análise filogenética comportamental: o caso dos mustelídeos - Bueno, Flávia Regina [UNESP] (2014)
The evolutionary relationships inside the Order Carnivora are extensively studied and sometimes contradictory, especially among caniforms. Although phylogenies based on molecular data have made a significant contribution, they can also be compared to reconstructions using other types of characters, such as the behavioral ones. Behavior has aided space on the current state of evolutionary biology, and among the various possible behaviors exhibited by animals, grooming is a very good source of phylogenetic characters. Grooming has stereotyped patterns and it has been shown that differences in patterns of grooming are observable between closely related species, which makes it a good source of phylogenetic characters. Thus this study aimed to reconstruct a phylogeny of the major families of caniforms carnivores using the grooming behavior as character. A molecular phylogenetic reconstruction was created for comparison and also as further evidence. In the behavioral reconstruction, except for the representatives of the external groups, it resulted a large polytomy. Terminals within this polytomy, however, present some interesting and highly bootstrap and jackknife supported associations. The results with molecular data, in which specific sectors of the cytochrome b gene were employed, showed a classical phylogeny of the suborder, except for the position of the Canidae‟s representative, but with low bootstrap support in most branches. Rapid adaptive radiation, recent speciation and great ecological diversity of the studied group turn difficult to establish the exact relationship between the terminals, independent of the biological data used.